THE INFLUENCE OF GENDER DIFFERENCES ON INSTAGRAM USAGE AMONG HIGHER INSTITUTION STUDENTS - Azureen Abd Aziz; Afiqah Abd Aziz (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
Instagram, the photo, and the video-sharing social medium are rapidly gaining popularity. Malaysia presents an excellent case for exploring the influence of culture on Instagram use. Like other developing countries, the traditional culture of Malaysia greatly affects the attitudes and behaviors of its people. It is interesting to examine the influence of gender on Instagram use activities. In Malaysia, the culture, besides security reasons, inhabits females from disclosing contact information. The central theme of this research paper is to understand gender differences in Instagram use by students in higher education students. This study uses the quantitative method where it involves 200 university students as the participants. The sample was selected among the students who take general studies in order to have a concrete result. This study confirms that males are more likely than females to post their personal pictures on Instagram, more likely to disclose their personal information, and more likely to have public accounts, unlike females who are more likely to have private accounts than males.